Step
*
2
of Lemma
derivative-function-rminus
1. f : ℝ ⟶ ℝ
2. f' : ℝ ⟶ ℝ
3. ∀x,y:ℝ.  ((x = y) 
⇒ (f'[x] = f'[y]))
4. d(f[x])/dx = λx.f'[x] on (-∞, ∞)
5. d(f[-(x)])/dx = λx.f'[-(x)] * -(r1) on (-∞, ∞)
⊢ d(f[-(x)])/dx = λx.-(f'[-(x)]) on (-∞, ∞)
BY
{ ((DerivativeFunctionality (-1) THEN Auto) THEN nRNorm 0 THEN Auto) }
Latex:
Latex:
1.  f  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
2.  f'  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
3.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (f'[x]  =  f'[y]))
4.  d(f[x])/dx  =  \mlambda{}x.f'[x]  on  (-\minfty{},  \minfty{})
5.  d(f[-(x)])/dx  =  \mlambda{}x.f'[-(x)]  *  -(r1)  on  (-\minfty{},  \minfty{})
\mvdash{}  d(f[-(x)])/dx  =  \mlambda{}x.-(f'[-(x)])  on  (-\minfty{},  \minfty{})
By
Latex:
((DerivativeFunctionality  (-1)  THEN  Auto)  THEN  nRNorm  0  THEN  Auto)
Home
Index